Program Pelatihan dan Pengembangan : Manfaatnya bagi Pegawai dan Organisasi Koperasi - Arman Maulana; Soeganda Priyatna; Husen Saeful Insan; Helmawati Helmawati (Coopetition : Jurnal Ilmiah Manajemen, 2021)
The purpose of this study is to present a literature study and observation that was established in the employee training and development program as well as the benefits of cooperatives in the ranks of the Cimahi City Dekopinda. This study analyzes the structure and elements of employee training and development programs and then this studio presents what are the positive results for employees and the Organization. Organizations find it difficult to stay competitive in the recent global economy. The importance of employee development plans is growing for Organizations seeking to gain an edge over competitors. Employees are a respected resource of the Organization and the success or failure of the Organization depends on the performance of the employees. Therefore, the organization finances a large number of employee training and development programs. Furthermore, the training program is very supportive for companies to emphasize the knowledge, skills and abilities of employees. There is substantial interest among professionals and researchers about the impact of development programs on employees and the organization. The study described here is an assessment of the literature on the basis of employee development programs and their benefits to organizations and employees.